Recent Advances in Carbon Nanotubes for Nervous Tissue Regeneration - Redondo, Carlos (2020)
Regenerative medicine has taken advantage of several nanomaterials for reparation of diseased or damaged tissues in the nervous system involved in memory, cognition, and movement. Electrical, thermal, mechanical, and biocompatibility aspects of carbonbased nanomaterials (nanotubes, graphene, fullerenes, and their derivatives) make them suitable candidates to drive nerve tissue repair and stimulation. -is review article focuses on key recent advances on the use of carbon nanotube- (CNT-) based technologies on nerve tissue engineering, outlining how neurons interact with CNT interfaces for promoting neuronal differentiation, growth and network reconstruction. CNTs still represent strong candidates for use in therapies of neurodegenerative pathologies and spinal cord injuries.